Equally Recognized? The Indigenous Peoples of Newfoundland and Labrador - Grammond, Sébastien (Osgoode Hall Law Journal, 2014)
In Canada, certain Indigenous groups are struggling to obtain official recognition of their status and rights. This is particularly so in Newfoundland and Labrador, where the authorities took the stance, when the province joined Canada in 1949, that no one would be legally considered Indigenous. This paper analyzes the claims of the Indigenous groups of that province, which have resulted, over the last thirty years, in various forms of official recognition. In particular, this article highlights how the concept of equality was used by these Indigenous groups to buttress their claims. Equality, in this context, was mainly conceived of as “sameness in difference”—that is, the idea that an unrecognized group claims to be treated consistently with other groups that share the same culture or identity and that are already officially recognized. Such assertions may be made in the context of human rights litigation, but also through joining or leaving associations of Indigenous groups. Through the latter process, unrecognized Indigenous groups of the province indicated to whom they wished to be compared and, in doing so, they ironically reinforced the hierarchy of statuses recognized under Canadian law.